Edukasi Interaktif Pencegahan Penyakit Campak bagi Orang Tua, Bayi, dan Balita di Posyandu Sri Rezeki - Mutiara Tsabitah Putri Miafy; Yasmin Fathina Saputra; Kathlia Irqazenia Lesmana; Hery Kurniawan (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
Measles is a highly contagious infectious disease that can be prevented through immunization and the practice of clean and healthy living. A lack of knowledge regarding measles prevention increases the risk of disease transmission. This health promotion activity aimed to improve public knowledge through educational sessions utilizing leaflets and educational videos at the Sri Rezeki Integrated Health Post (Posyandu) in Rawasari, Samarinda. The activity employed a one-group pretest-posttest design involving 40 participants. Knowledge was assessed using a 10-item multiple-choice questionnaire administered before and after the session, with data subsequently analyzed using the Wilcoxon test. The median knowledge score increased from 8 in the pre-test to 10 in the post-test. The Wilcoxon test revealed a significant difference between the pre-test and post-test scores (p < 0.001). Subgroup analysis indicated that age was significantly associated with the improvement in knowledge (p = 0.034), whereas gender, occupation, and education level were not. These findings demonstrate that leaflets and educational videos are effective in enhancing public knowledge and have the potential to be implemented in health education programs to support sustainable measles prevention.